Families and Collective Futures: Developing a Program Logic Model for Arts-Based Psychosocial Practice With South African Rural Communities - Havsteen-Franklin, Dominik; Swanepoel, Marlize; Jones, Jesika; Conradie, Uné (Frontiers in Psychology, 2021)
Aim: This aim of this study is to describe the development of a program logic model to guide arts-based psychosocial practice delivered in rural South African farming communities affected by transgenerational traumas. Background: The rationale for developing a program logic model for arts-based psychosocial practice in South Africa was based on the lack of evidence for effective community arts-based psychosocial interventions for collective trauma, unknown consensus about best practices and the need for developing cogent collective psychosocial practices. Further to this, the aims and benefits of the practice required clarity given the psychosocial complexity of the environment within which the practices for this population are being offered. The logic model offers a valuable resource for practitioners, participants and funders to understand the problem being addressed, how practice is defined, as well as the impact of practice and on intermediate and longer term goals. Methods: The authors used a systematic iterative approach to describe the operationalization of arts-based psychosocial practice. This resulted in the design of the logic model being informed by data from focus groups, an overview of the literature regarding transgerenational trauma in this population, operational policies and organizational documents. The development of the logic model involved actively investigating with practitioners their work with remote farming communities. We thematised practitioners practice constructs to identify salient practice elements and their relationship to perceived benefits and lastly feedback from practitioners and participants following implementation to make adjustments to the logic model. Results: The results were clearly identified in the form of visual mapping using the design of a program logic model. The logic model was divided into 5 parts and was verified by practitioners following implementation. The parts of the program logic model are (Part 1) main presenting problem, (Part 2) operational processes, (Part 3) practice elements, (Part 4) benefits, and impact and (Part 5) review.